(untitled) (Journal of Social Sciences Review, 2023)
The present research is the study of linguistic variations in the language of males and females in the movie North Country. By applying Robin Lakoff’s deficit theory to the work, the research highlighted the difference based on hedging, tag questions, and intensifiers. Language variation in gender was a common topic in the 1970s, but till now not much empirical evidence is present to support Robin Lakoff’s theory, the research has provided a firm ground for the theory. The research study is a qualitative and quantitative analysis of the discourse of males and females in the movie "North Country." The research study findings in accordance with its objectives show how male and female’s language differs from each other by providing empirical evidence, as males and females show different trends in the use of tag questions, hedging, and intensifiers. This is a highly significant study academically it will provide analyzed data with evidence to students of genderlect.